Regional Labor Market Disparities in Belgium - Estevão, Marcello M. (International Monetary Fund, 2002)
Regional labor market discrepancies have been widening in Belgium in the last two decades and are more evident within particular demographic groups. These developments can largely be accounted for by worse matching of people to jobs in the high-unemployment provinces. Using a structural VAR, it is also shown that labor market dynamics in Belgium produce a strong attenuating effect on employment growth, in contrast to the United States where initial labor demand shocks are expanded in the long run. After the short-run adjustment is over, there is less labor migration in Belgium than in the United States or Europe, corroborating the perception that Belgians move ""too little